Música para una venganza. Racismo, violación y asesinato el caso de El último tren de Gun Hill (John Sturges, 1959) - Lucía Pérez García (Ambigua, 2020)
The Western film directed by the American filmmaker John Sturges, The Last Train from Gun Hill (1959), tells the story of a man’s revenge for the rape and murder of his Native American wife. The music, composed by Dimitri Tiomkin -in the third collaboration with Sturges, plays a fundamental role in the narrative shaping. For this, the composer usesonce again the monothematic technique that made him successful in the fifties and in his previous western with the director, Gunfight at OK Corral(1957), becoming the reference point of the Western film music since High Noon(Fred Zinnemann, 1952). Analyzing the score and the scrip and comparing them with those of the two other works in which Tiomkin had to deal with rape and vengeance, it is proved that the whole music of The Last Train from Gun Hill gives voice to the outraged woman, who uses the various characteristics and variations of the main theme to guide the actions of the male protagonist. This way, it is confirmed the Tiomkin’s ability to highlight the female characters of his films -whether they are protagonists or have a supporting role; as well as the possibility of addressing from different points of view such serious issues as rape, murder, vengeance and even racism, through the film music.